DEVELOPMENT OF INFORMATION COMPETENCIES AND COMPUTER LITERACY OF SECONDARY SCHOOL GRADUATES - RÉVÉSZOVÁ, Libuša (Journal of Technology and Information Education, 2012)
The article summarizes results of the research of information competencies and computer literacy of secondary school graduates who entered the first grade at the Economics Faculty Technical University in Košice. We compared the results of questionnaires from 2003-2005 and 2009-2011.
Keywords: education; information competences; computer literacy